2016
DOI: 10.1680/jadcr.15.00139
|View full text |Cite
|
Sign up to set email alerts
|

Acid resistance of calcium aluminate cement–fly ash F blends

Abstract: The short-term resistance to sulfuric acid at 90°C of four calcium aluminate cement (CAC)-fly ash class F (FAF) blends activated with sodium metasilicate (thermal shock resistant cements (TSRCs)), cured at 300°C, was compared to that of a calcium phosphate cement (CPC) (CAC-FAF blend activated with sodium hexametaphosphate) and a Portland cement class G/silica blend. The mechanical properties and compositions of the acid-exposed samples were evaluated by measuring their compressive strength and by means of x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 51 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Sulfuric acid can also be present in groundwater or produced from the oxidation of sulphur bearing compounds in backfill, such as pyrite, causing degradation to concrete substructures [13]. The dissolution of hydrogen sulphide can also form sulfuric acid with a low pH on the concrete walls of geothermal wells [14]. Therefore, sulfuric acid is a major cause of degradation of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid can also be present in groundwater or produced from the oxidation of sulphur bearing compounds in backfill, such as pyrite, causing degradation to concrete substructures [13]. The dissolution of hydrogen sulphide can also form sulfuric acid with a low pH on the concrete walls of geothermal wells [14]. Therefore, sulfuric acid is a major cause of degradation of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral features closely resembled each other containing the same frequency nine representative frequency bands with the following contributors. The C-O (V as C-O ) stretching vibration in carbonate CO 3 2− emerged in the region of 1510 to 1400 cm −1 [63,64,65], the Si-O-Si linkage-associated V as Si-O vibration in silica gel at 1243 cm −1 [66,67,68], the Al-OH bending (δ as Al-OH ) and (δ s Al-OH ) vibrations, and AlO 4 tetrahedral (V Al-O ) stretching in bohmite (γ-AlOOH), were respectively, at 1148, 1068, and 777 cm −1 , reflecting the presence of typical bohmite-related doublet peaks of O-H group at 3307 (V as O-H ) and 3086 (V s O-H ) cm −1 bands (not shown) [69,70,71,72], the M-O (M: Si or Al) (V as M-O ) in amorphous and crystalline Na 2 O-Al 2 O 3 -SiO 2 -H 2 O (N-A-S-H), CaO-Al 2 O 3 -SiO 2 -H 2 O (C-A-S-H), and CaO,Na 2 O-Al 2 O 3 -SiO 2 -H 2 O (C,N-A-S-H) hydrates appeared at 990 and 902 cm −1 [73,74,48], and the Si-O stretching (V s Si-O ) and Si-O bending (δ O-Si-O ) modes in quartz at 738 and 675 cm −1 , respectively with a possible quartz contribution to the band at 1068 cm −1 (V s Si-O ) [62]. The N-A-S-H, C-A-S-H, and C,N-A-S-H phases were assembled by the interactions between Na + and Ca 2+ released by SMS activator and CAC, and the aluminosilicate anhydrous compounds in FAF [75].…”
Section: Resultsmentioning
confidence: 99%
“…High temperature hydration of TSRC results in calcium-aluminum silicates, zeolite-family crystalline products and (C,N)-A-S-H amorphous phase [ 43 , 73 ]. The crystalline calcium-aluminum-silicate hydrates include hydrogrossular phases at earlier hydration times (katoite, grossular, and hibschite) and feldspar (dmisteinbergite and anorthite) or feldspathoid (cancrinite in carbonate-rich environment) type minerals after longer curing at temperature above about 250 °C.…”
Section: Discussionmentioning
confidence: 99%
“…CaP also forms carbonated apatite. In the case of sulfuric acid attack calcium reacts with sulfates forming anhydrate in both cements and the remaining alkali aluminum-silicates provides structural stability of the acid-treated matrix [22].…”
Section: Componentmentioning
confidence: 99%
“…Studies on alkali-activated cement composite of calcium aluminate cement and fly ash F (thermal shock resistant cement, (TSRC)) demonstrated excellent performance under various stresses of simulated geothermal environments [21,22], and outstanding CS bond durability [23]. Further work showed that TSRC has self-healing properties, which is ability to recover its compressive strength and seal the cracks at temperatures up to 300°C [24].…”
Section: Introductionmentioning
confidence: 99%